2015
DOI: 10.1007/978-3-642-36833-2_21
|View full text |Cite
|
Sign up to set email alerts
|

Depth of Melt Segregation Below the Nyos Maar-Diatreme Volcano (Cameroon, West Africa): Major-Trace Element Evidence and Their Bearing on the Origin of CO2 in Lake Nyos

Abstract: The Nyos maar-diatreme volcano on the Oku Volcanic Group (OVG) in NW Cameroon carries yet the most infamous maar lake in the world because the lake exploded in 1986 releasing CO 2 that killed *1,750 people and over 3,000 livestock. A process of safely getting rid of accumulated gas from the lake started in 2001. Even though *33 % of it has been removed, gas continues to seep into the lake from the mantle, so the lake still poses a thread. Available data on basaltic lava from the maar-diatreme volcano and other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 110 publications
0
6
0
Order By: Relevance
“…In particular, looking at the Lake Nyos and Monoun disasters (e.g., Kling et al, 1986;Kusakabe et al, 1989;Le Guern et al, 1992), the scientific community is still debating the type of eruption involved. These two disasters prompted research and there is a permanent interest in studying maar volcanism in the area though most investigations are concentrated on Nyos and Monoun maars (e.g., Issa et al, 2013;Aka, 2015;Kusakabe, 2015).…”
Section: Geological Settingmentioning
confidence: 99%
“…In particular, looking at the Lake Nyos and Monoun disasters (e.g., Kling et al, 1986;Kusakabe et al, 1989;Le Guern et al, 1992), the scientific community is still debating the type of eruption involved. These two disasters prompted research and there is a permanent interest in studying maar volcanism in the area though most investigations are concentrated on Nyos and Monoun maars (e.g., Issa et al, 2013;Aka, 2015;Kusakabe, 2015).…”
Section: Geological Settingmentioning
confidence: 99%
“…In addition, the report of the temperatures obtained in this work in the P-T diagram of Mercier and Carter [47] applicable for rifting context, we estimate the pressures from 8 to 18 Kbar corresponding to depths of 50 to 30 km (Figure 11 and see text for explanation), pressures in which studied xenoliths were incorporated in the host lavas, except sample NK14. [48]. The curves correspond to the different possible experimental evolutions depending on the depth.…”
Section: Discussionmentioning
confidence: 99%
“…Aka [48] indicates that the depth of melt segregation below the Nyos maardiatreme volcano is shallower. The supposed shallow depth of the asthenophere beneath the LNVU indicates that the deepest xenoliths brought up by the basaltic eruption originate from a mantle region not much shallower than the source regions of basaltic magma.…”
Section: Discussionmentioning
confidence: 99%
“…Lake monitoring studies showed that the killer gas in both lakes was magmatic carbon dioxide. The lakes are currently being degassed artificially [8] [9]. Floods are common in urban and rural areas and are on the rise in major cities.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to large-scale infrequent disasters like volcanic eruptions, earthquakes, and gas explosions from volcanic crater (maar) lakes ( [9], most small-scale everyday disasters are not well reported in Cameroon, despite the fact that cumulatively, they cause the most casualties and distress to the often very poor people affected [13] [14]. This can flaw the inventory and evaluation of economic impacts of disasters in the country particularly for landslides found in remote areas.…”
Section: Introductionmentioning
confidence: 99%